Neutron radiography as a tool for assessing penetration depth and distribution of a phosphate consolidant for limestone. (30th October 2018) - Graziani, Gabriela; Colombo, Chiara; Conti, Claudia; Possenti, Elena; Perelli Cippo, Enrico; Realini, Marco; Sassoni, Enrico
Highlights: Consolidants are applied to re-establish cohesion among grains in weathered stones. Neutron radiography (NR) was used to study distribution of a phosphate consolidant. Three application methods were compared (brushing, poulticing, partial immersion). Homogeneity of the consolidant distribution can be reliably evaluated by NR. Penetration depth can be reliably evaluated by combination of NR with FT-IR and XRD. Abstract: Neutron radiography was used to determine the penetration depth and the homogeneity of distribution of an innovative inorganic consolidant, based on formation of hydroxyapatite. The consolidant was applied to a porous limestone by three alternative methods (brushing, poultice, partial immersion). Neutron radiography was complemented by XRD, FT-IR and SEM/EDS, which provide information also on mineralogical composition and morphology of the new phases. Neutron radiography proved to be a powerful tool to determine the presence of hydrogen-rich hydroxyapatite and to evaluate the homogeneity of its distribution in the substrate. Nonetheless, combination with other techniques is necessary to reliably assess its penetration depth.